Synthesis and Characterization of Ag@C-TiO2 Nanocomposite for Degradation of Sasirangan Textile Wastewater - Heny Puspita Dewi; Joko Santoso; Nur Firda Trianda; Rodiansono Rodiansono (Jurnal Kimia Sains dan Aplikasi, 2019)
Carbon-titanium oxide nanocomposite (denoted as @C-TiO2) was successfully synthesized via hydrothermal method at 150°C for 24 h. The C-TiO2 nanocomposite was furtherly modified by adding an Ag metal dopant (denoted as Ag@C-TiO2) to improve and applied to the photocatalytic degradation of Sasirangan textile wastewater. The composite photocatalysts were characterized by XRD and UV–Vis DRS spectroscopies. XRD patterns showed that TiO2 in @C-TiO2 mainly consisted of a brookite phase, as indicated by a series sharp diffraction peak at 2θ = 27.2° (111), 31.5° (121) and 55.9° (241). The calculated band gap energy (Eg) derived from UV-Vis DRS spectra for TiO2, @C-TiO2, and Ag@C-TiO2 were 2.95 eV, 2.54 eV, and 2.74 eV, respectively. Ag@C-TiO2 photocatalyst was found to be active for the photocatalytic degradation of Sasirangan textile wastewater, as indicated by the change of wastewater color from dark to clear. The quantitative photocatalytic activity of Ag@C-TiO2 was evaluated in the degradation of methylene blue, whereas the conversion of methylene blue was 41.3%. The addition of Ag to @C-TiO2 is believed to play an essential role in the enhancement of photocatalytic activity.